Identities of Symmetry for Higher-Order Generalized q-Euler Polynomials - D. V. Dolgy; D. S. Kim; T. G. Kim; J. J. Seo (Abstract and Applied Analysis)
We investigate the properties of symmetry in two variables related to multiple Euler q-l-function which interpolates higher-order q-Euler polynomials at negative integers. From our investigation, we can derive many interesting identities of symmetry in two variables related to generalized higher-order q-Euler polynomials and alternating generalized q-power sums.